Eksplorasi Camilan Wonton dan Keju Aroma : Sosialisasi Demo Masak sebagai Bentuk Pengabdian Masyarakat - Insania Machmuda; Rina Andriani; Dyna Arofatul Baiyinah; Adia Hilar Hilabi; Rizky Dwi Setiawan; Virginia Mandasari (Universitas 17 Agustus 1945 Semarang, 2023)
This research is related to socialization activities that will help UMKM develop their products so they can compete in a tight market. This activity exists because of observations that the region has many UMKM that focus on the food sector. The cooking demonstration activity was chosen because the delivery of the cooking recipe steps was easy to follow for the participants, who were dominated by mothers. A cooking demonstration is an activity that explains the process of cooking a dish in a coherent and detailed manner so that it can be easily understood. Food that is trendy and popular with many groups is an important factor in menu selection. This activity aims to help UMKM innovate their products so they can compete competitively and is easy to understand.